Revenue Administration Reform in Middle Eastern Countries, 1994-2004 - Bodin, Jean-Paul (IMF Working Papers; Working Paper, 2005)
The paper provides an overview of revenue administration reforms implemented in Middle Eastern and North African countries over the past decade with IMF assistance. Although reforming tax and customs administration is neither quick nor simple, several countries in the region have embarked on comprehensive programs of reforms to modernize their revenue administration, and encouraging progress has been achieved. Experience shows that there are many challenges to be faced and that critical requirements need to be met, including political commitment, strong leadership, willingness to abandon ineffective practices; and establishment of reform projects with clear mandates, agreed objectives, and realistic timeframes.